Land use/land cover dynamics in the northern watershed of lake Tana: implications for water quality - Engdaw, Flipos; Fetahi, Tadesse; Kifle, Demeke (Frontiers in Environmental Science, 2024)
Uncontrolled land use/land cover (LU/LC) change brought by rRapid population growth,induced urbanization, industrialization, deforestation, and settlement expansion and habitat destruction pose are significant drivers of LU/LC change at global scale. The uncontrolled LU/LC change, specifically environmental threats to water quality deterioration and biodiversity impoverishment in developing countries like Ethiopia, poses significant environmental threats to water quality, biodiversity, and ecosystem services. This study, So far, there has been paucity of information regarding LU/LC change and its implication for water quality in the northern watershed of Lake Tana. Ttherefore, examined this study assessed trends in LU/LC trends in the Lake Tana catchment, Ethiopia fromand how changes affected water quality between 1993 to and 2022, analyzed the impact of changes on water quality and identified major drivingfactors for policy input. The study used ArcGIS software and Landsat imagery, were employed to and produced maps for 10 years. Water quality data were obtained from primary and secondary sources fromr 2002 to 2022. The relationship between LU/LC changes and water quality was examined using Pearson"s correlation and principal component analysis (PCA). were used to correlate the land cover changes and water quality. Results revealed significant (p<0.05) spatiotemporal variations in water quality parameters, with almost all parameters showing a substantial increase from 2002 to 2012 and some declined in 2022. LU/LC changes were categorized into six classes with an overall accuracy and Kappa coefficient of 92.2% and 0.86%, respectively.Various LU/LC classes were highly correlated with a particular water quality parameter.Expansion of sSettlement and crop land expansion were positively correlated with nutrients such as (NH 3 -+ NH 4 + -N), NO 3 -N, SRP and TP. demonstrating a strong linkage between LU/LC and water quality. However, fForestation was positively correlated with increased good water quality including such as DO and , pH, while they were negatively correlated with temperature, EC, SRP and NO 3 -N demonstrating a strong linkage between LU/LC and water quality. These findings Ttherefore, validate the significance of prioritizing LU/LC changes is crucial for sustainable water quality and ecosystem service improvement of in the Lake Tana catchment.